The effect of meal from the larvae of the Black soldier fly (Hermetia Illucens) on the lipid metabolism of breeding chickens of the “Highsex brown” cross - Romanenko Evgenia; Busheva Anna (BIO Web of Conferences)
The results of the research presented in the article are devoted to the study of the effect of feeding black soldier fly larvae (Hermetia illucens) instead of soybean meal on lipid metabolism and egg production of breeding hens of the Hisex Brown cross. The inclusion of the new feed (10%) in the diet of hens of the experimental group led to the activation of lipid metabolism. A reliable (P “ 0.05) increase in the content of total lipids, phospholipids and triglycerides in the blood serum of breeding hens was recorded. The level of low-density lipoproteins decreased to 2.23 mmol / l against 2.56 mmol / l in the control, and high-density lipoproteins increased by 6.43%. The lipid composition of the yolk of hatching eggs of the experimental group also underwent changes: the level of total lipids increased by 9.43% (P “ 0.05), triglycerides - by 11.30% (P “ 0.05). A stable increase in phospholipids in the experimental group against the control group by 7.14%, lecithin in their composition by 5.83% was noted. An increase in the intensity of egg production in hens by 2.47%, the yield of incubatory eggs by 1.60, egg hatchability by 2.77%, and chicken hatchability by 2.04% was established. An increase in the intensity of egg production in hens by 2.47%, the yield of incubatory eggs by 1.60, egg hatchability by 2.77%, and chicken hatchability by 2.04% was established.